ANALISIS PERANAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PENINGKATAN PROFITABILITAS DAN NILAI PERUSAHAAN : STUDI KASUS PADA PERUSAHAAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2012 - Santoso, Cahyo Budi (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
Corporate Social Responsibility (CSR) company is one form of concern for the environment of a company. Currently CSR aims to maximize profits but also are required to accomodate the needs of the community and its stakeholders. This study aimed to provide the result of CSR effects on profitability and company firm value.This study samples using cement companies listed at Bursa Efek Indonesia (BEI) period 2010-2012. The data used is the company’s financial report released every year. The results showed that during the period 2010-2012 CSR value has significant impact on company profitability using financial ratio Return on Equity (ROE). Then, this study also showed the influence of CSR on firm value using financial ratio Price Earning Ratio (PER).The result showed that Corporate Social Responsibility (CSR) affect profitability and firm value. For future research can add the independent variable, or add proxy profitability.Key word: Corporate Social Responsibility (CSR), profitability (ROE), firm value (PER).